Emergency Sonography Aids Diagnostic Accuracy of Torso Injuries: A Study in a Resource Limited Setting - Tunuka, Charles Edward; Wangoda, Robert; Bugeza, Sam; Galukande, Moses (Emergency Medicine International, 2014)
Introduction. Clinical evaluation of patients with torso trauma is often a diagnostic challenge. Extended focused assessment with sonography for trauma (EFAST) is an emergency ultrasound scan that adds to the evaluation of intrathoracic abdominal and pericardial cavities done in FAST (focused assessment with sonography for trauma). Objective. This study compares EFAST (the index test) with the routine standard of care (SoC) investigations (the standard reference test) for torso trauma injuries. Methods. A cross-sectional descriptive study was conducted over a 3-month period. Eligible patients underwent EFAST scanning and the SoC assessment. The diagnostic accuracy of EFAST was calculated using sensitivity and specificity scores. Results. We recruited 197 patients; the M : F ratio was 5 : 1, with mean age of 27 years (SD 11). The sensitivity of EFAST was 100%, the specificity was 97%, the PPV was 87%, and the NPV was 100%. It took 5 minutes on average to complete an EFAST scan. 168 (85%) patients were EFAST-scanned. Most patients (82) (48%) were discharged on the same day of hospitalization, while 7 (4%) were still at the hospital after two weeks. The mortality rate was 18 (9%). Conclusion. EFAST is a reliable method of diagnosing torso injuries in a resource limited context.